KEGIATAN TEMU SEDULUR DAN SYAWALAN KAMESADHA: KUANTIFIKASI STATISTIK GAGASAN ALUMNI - Astyanto, Achilleus Hermawan; Yoanita, Yulia Venti (Universitas Sanata Dharma, 2023)
The management of the board of KAMESADHA for the 2021–2024 period was definitively established during a mechanism of general election. In a particular mission, the board should enhance the communication, synergy, and collaboration among the stakeholders, i.e. alumni and the university. The present work elaborates a statistical quantification on the ideas of the members of KAMESADHA regarding how important the alumni gathering is. A typical result reveals an annual gathering concerning the corresponding synergy is suggested.